System technical solution of electromagnetic adaptation - Rustamov, Asad; Hashimov, Elshan; Ganjiyev, Amil; Rahimli, Vusal; Hashimov, Ruslan (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article describes the main schematic and technical solutions for electromagnetic compatibility in military radar equipment. In addition to the selection scheme, a method for synchronizing the operation of several radar stations that are very close to each other or operate at the same repetition frequency is studied. The purpose of the research is to analyze the electromagnetic compatibility system in military radar devices. In accordance with this goal, the scientific research work sets forth the following tasks: analysis of the electromagnetic compatibility system in military radar devices; selection, provision, or, if necessary, modification of the system's operating principle; consideration of the planning and distribution of the radio frequency source among the elements included in the analyzed system; practical application of the approach based on the joint selection of electromagnetic compatibility, reduction in their number, and introduction of various simplifying assumptions, etc.; analysis of the general problem of solving the problem of parameters.

У статті описано основні принципові та технічні рішення забезпечення електромагнітної сумісності радіолокаційної техніки військового призначення. Крім схеми вибору, досліджується метод синхронізації роботи кількох радіолокаційних станцій, які знаходяться дуже близько одна до одної або працюють на одній частоті повторення. Метою дослідження є аналіз системи електромагнітної сумісності радіолокаційних пристроїв військового призначення. Відповідно до цієї мети в науково-дослідній роботі ставляться наступні завдання: аналіз системи електромагнітної сумісності радіолокаційних пристроїв військового призначення; вибір, забезпечення або, за необхідності, модифікація принципу роботи системи; розгляд планування та розподілу джерела радіочастот між елементами, що входять до аналізованої системи; практичне застосування підходу, заснованого на спільному виборі електромагнітної сумісності, зменшенні їх кількості та введенні різноманітних спрощуючих припущень тощо; аналіз загальної задачі вирішення задачі параметрів.
Системно-технічне рішення електромагнітної адаптації
Keywords: system engineering solutions; selectors; synchronizers; regulatory devices; electromagnetıc adaptatıon; електромагнітна адаптація; системно-технічні рішення; селектори; синхронізатори; регулюючі пристрої; військова радіолокаційна техніка